Magnetic measurements of the 63-pole 2 Tesla superconducting wiggler for Canadian Light Source - Bekhtenev, E.A.; Kuzin, M.V.; Khruschev, S.V.; Mezentsev, N.A.; Miginsky, E.G.; Shkaruba, V.A.; Tsukanov, V.M. (Вопросы атомной науки и техники, 2006)
The magnet measurement methods for a multipole superconducting wiggler using the Hall probes and stretched wire are described. The results of magnet measurements for the 63-pole superconducting wiggler are presented. The measurements have been carried out in the bath cryostat (with the Hall probes temperature 4.2 K) as well as in its own cryostat using a special scanning room temperature antechamber. Описаны методы магнитных измерений для многополюсного сверхпроводящего вигглера с использованием датчиков Холла и натянутой проволоки с током. Приведены результаты магнитных измерений 63-полюсного сверхпроводящего вигглера в погруженном (при температуре датчиков Холла 4.2 К) и собственном (с иcпользованием специальной сканирующей аванкамеры комнатной температуры) криостатах. Описано методи магнітних вимірів для багатополюсного надпровідного вігглера з використанням датчиків Холу й натягнутого дроту зі струмом. Наведено результати магнітних вимірів 63-полюсного надпровідного вігглера в зануреному (при температурі датчиків Холу 4.2 К) і особистому (з використанням спеціальної скануючьої аванкамери кімнатної температури) кріостатах.